Answer:
y=2x^2 + 2x - 3 x -2 -1 0 1 2
Step By Step Explanation:
The values can be find by plugging the x values in the equation which gives us the y value ,
x -2 -1 0 1 2
y 1 -3 -3 1 9
(b) Plot the points on the graph and join by a smooth curve.
(c) The line y=1 will be passing through 1 and parallel to x-axis.
(d) solve 2x^2 + 2x - 3 = 1
Subtract 1 from both the sides ,
2x^2 + 2x - 2 = 0
Factoring out the 2 from the equation ,
2(x^2 + x - 1) = 0
x^2 + x - 1 = 0
Apply the quadratic formula
x=(-1-sqrt(5))/2 and x = (-1+sqrt(5))/5